DO ANTHROPOLOGISTS USE RATIONAL ACTOR MODELS? THE CASE OF MARILYN STRATHERN - Terence Rajivan Edward (IJRDO - Journal of Social Science and Humanities Research, 2022)
Economics uses rational actor models, but what about anthropology? I present an interpretation of the influential anthropologist Marilyn Strathern according to which she engages in a kind of rational actor modelling, but a kind that is different from economic modelling.